Pengaruh Kualitas Produk Tabungan Wadiah Terhadap Keputusan Nasabah Menabung Di PT. Bank Sumut Syariah KCP Stabat - Tata Irmala; Azhar Azhar (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2023)
This study aims to determine the effect of the quality of wadiah savings products on customer decisions to save at PT. Bank SUMUT Syariah KCP Stabat. This type of research is quantitative research using two data sources, namely primary and secondary. Data analysis uses classical assumption tests, hypothesis tests, and simple linear regression analysis. The results showed that there was a significant influence between the quality of wadiah savings products on savings decisions at PT. Bank SUMUT Syariah KCP Stabat. This is evidenced from data analysis using hypothesis tests, namely the t test which shows more signification values smaller than 0.05 or (0.000 0.05) and t count t table (6.628 1.98729) then there is an influence of variable X on Variable Y. The quality of wadiah savings products affects the decision of customers to save at PT. Bank SUMUT Syariah KCP Stabat by 32.5%. There is a positive or inconsistent relationship between the quality of wadiah savings products and the decision to save at PT. Bank SUMUT Syariah KCP Stabat, the better the quality of wadiah savings products offered by PT. Bank SUMUT Syariah KCP Stabat then further improves the decision to save, and vice versa, the better the quality of wadiah savings products offered by PT. Bank SUMUT Syariah KCP Stabat has further reduced the decision to save.